Overview of Religious Activities of Students in Makassar in the Third Year of Covid-19 - Hapsah, Hapsah; Sabriyati, Wa Ode Nur Isnah; Rustam, Andi Tenri; Mikan, Anugrahwati Datu; Fitriani, Nurlaila; Saleh, Ariyanti; Hamisah, Hamisah (Indonesian Contemporary Nursing Journal (ICON Journal), 2023)
Aims: This study aims to describe the religious activities of students at a public institution in MakassarMethods: This descriptive survey was conducted on students who are actively registered and willing to be respondents with a total sampling period of 30 days (26 September - 28 October 2022) (n = 1,207). Informed consent was given by the team both offline and online. The religious activity questionnaire was given in the form of an online form while still adhering to the ethical principles of research.Results: The results showed that the religious activities of Muslim students for 7 religious activities including prayer, fasting, reading the Qur'an, Islamic interpersonal relationships (dominantly practice good morals (59.6% - 93.4%), alms (more than a half sometimes (60.6%)), learn Islam (never = 49.9%), and remembrance and prayer activities (most widely sometimes (35.8%-48.6%). For Christian religious activities with 3 domains, worship activities (spiritual discipline) (91.2% follow Sunday worship and 90.4% private prayer with main prayer, religious attitude (more than 80% always do religious attitude) and relationships with others.Conclusion: Students' religious activities need to be improved for wellness and happiness because many still have not actively implemented their religious teaching. Therefore, it is required to make an effort to increase religious activities as part of spiritual coping to leverage the mental health welfare of students.